Locking compression plate: a treatment option for diaphyseal nonunion of radius or ulna - Ling, H.T.; Kwan, M.K.; Chua, Y.P.; Deepak, A.S.; Ahmad, T.S. (MJM, 2006)
Treatment of radius or ulna nonunion requires both osteogenic environment and mechanical stability. We would like to report three radial and six ulnar diaphyseal nonunions treated with 3.5 mm locking compression plate (LCP) fixation. To assess the effectiveness of 3.5 mm LCP in treating diaphyseal nonunion of the forearm bones, we prospectively reviewed nine patients with the mean age of 33 years with diaphyseal nonunion of the radius or ulna. All patients were treated with 3.5 mm LCP. Bone grafting was only performed for atrophic nonunion. Surgical and functional outcome were evaluated. There were three atrophic nonunion of the radius, four atrophic nonunion of the ulna and two hypertrophic nonunion of the ulna. All nonunion united successfully with satisfactory functional outcome. 3.5 mm LCP is effective in the treatment of nonunion of ulna or radius.